Analysis on the expression and function of syndecan in the Pacific white shrimp Litopenaeus vannamei. Issue 2 (August 2015) - Yang, Hui; Li, Shihao; Li, Fuhua; Wen, Rong; Xiang, Jianhai
Highlights A full length cDNA of syndecan gene (LvSDC) was isolated from Litopenaeus vannamei. The expression of LvSDC was apparently up-regulated after WSSV infection. Silencing of LvSDC could reduce the mortality of shrimp caused by WSSV infection.